(untitled) (शोधसुधा Shodh Sudha, 2024)
This paper offers a critical analysis of the English curriculum at Nepal Sanskrit University, focusing on its structure, content, and implementation strategies. The curriculum, designed to provide students with a comprehensive exploration of the English language and literature, reflects a balance between tradition and modernity. Through an examination of core components such as reading and writing skills, literary analysis, and research writing, the paper assesses the strengths and weaknesses of the curriculum. Drawing on insights from stakeholders, including faculty and students, it explores challenges such as resource limitations and the need for real-world English study contexts. Furthermore, it discusses opportunities for innovation and enhancement, including the integration of technology and collaboration with interuniversity institutions. By navigating the landscape of the English curriculum at Nepal Sanskrit University, this paper aims to provide valuable insights into its continual refinement and relevance in the ever-changing educational landscape.